LOGICAL FALLACIES ON STUDENTS’ ARGUMENTATIVE WRITING - Leli Lismay (Universitas Mahaputra Muhammad Yamin, 2020)
In writing an argumentative paragraph, there will be some fallacies that can be explained as students’ misunderstanding in interpreting source language to target language, in this context English is as a target language. This misunderstanding called logical fallacies where it can broke the meaning in TL. Therefore, the aim of this research was to identify and analyze types of logical fallacies done by the fourth semester students in argumentative writing at English department of IAIN Bukittinggi. The design of this research was descriptive quantitative. The population was the fourth semester students who take writing for professional context subject. The sample was 28 students. The instrument used was documentation of student’s argumentative writing tasks. The result showed that, some informal logical fallacies found in students’ writing. 76% students wrote inductive fallacy on their writing which means that students drew a conclusion without providing enough evidence on their writing.